Sulphur isotope study of pyrite from the Twangiza-Namoya Gold Belt, (South Kivu, DRC): a proxy of gold provenance - Moloto, Thapelo Refiloe Patience (Rhodes University, Faculty of Science, Department of Geology, 2018)
Gold in the highly prospective Twangiza-Namoya Gold Belt (TNGB) in the eastern Democratic Republic of Congo (DRC), with its four main deposits at Twangiza, Kamituga, Lugushwa and Namoya, appears to be correlated with the presence of sulphide minerals. Sulphur isotopic compositions of pyrite in the metasedimentary host rocks and in hydrothermal veins are used to identify the possible primary sources of hydrothermal sulphur and, by proxy, hydrothermal gold. The sulphur isotope signatures of the pyrites from the TNGB deposits show an overall range from -18.4%o to +22.6%o. S34 values in host rock pyrite are: -2.2%o to +3.0%o (Twangiza deposit), -4.2%o to -0.6% (Kamituga deposit), -18.4% to -12.7% (Lugushwa deposit), and +12.4% to +22.6% (Namoya deposit). The sulphur isotopic signature of vein pyrite is -5.2% to +3.0% (Twangiza deposit), -9.1% to -7.4% (Kamituga deposit), -0.3% to +3.2% (Lugushwa deposit) and +1.3% to +20.4% (Namoya deposit). The isotopic data indicate a primary sedimentary to evaporitic source of sulphur in the host rock pyrite. Pyrite from metadiorites shows magmatic S isotope compositions. Native gold was found in both sedimentary host rock and vein samples. This indicates that native gold was present in the primary metasedimentary sequence of the TNGB. Some vein pyrites in the TNGB have isotopic signatures that are similar to that of the host rock pyrite. These veins have formed from fluids extracted from the hosting metasedimentary sequence. Conversely, other vein pyrite shows different S34S values compared to the host rock pyrite, suggesting a fluid source that is different from the sedimentary source. Possibly, particularly in the Lugushwa deposit, an igneous source may have released sulphur and possibly gold bearing fluids in addition to those extracted from the sedimentary sequences in the TNGB. However, there is abundant evidence for sulphur and gold mobilised in the sedimentary host rocks and precipitated in the hydrothermal system of the TNGB.
Keywords: Isotope geology -- Congo (Democratic Republic); Pyrites -- Congo (Democratic Republic); Gold mines and mining -- Congo (Democratic Republic); Sulfur -- Isotopes -- Congo (Democratic Republic); Hydrothermal deposits -- Congo (Democratic Republic); Twangiza-Namoya Gold Belt, (South Kivu, DRC)